THE EFFECT OF ADDITIVE TYPE "X" WITH FOAM AGENT AND COCONUT FIBER ON CONCRETE - Abdul Muhaimin; Fredy Kurniawan (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
One of the building materials that has developed very rapidly is concrete. Some of the advantages of concrete include the relatively low price, high compressive strength, rust resistance, easy transport and printing, and are relatively resistant to fire. There are several ways that can be used to make concrete light, including the use of lightweight aggregates, foam agents, coconut fibers and additive types "x", where coconut fiber waste has not been used optimally. In this study a lightweight concrete mixture of additive type "was made using x 5M additive products, foam agents and coconut fibers using a cement content of 650kg / m3. The variation of the "x" additive is 2%, 4%, 5%, foam agent is 2.5%, 3%, 4% and coconut fiber is 15%, 20%, 25%. with the treatment conditions for the specimens for 28 days soaked and not soaked. Test objects are made of cubes with a size of 15x15x15cm. This study is to determine the weight / m3, the compressive strength of the lightweight concrete produced. The results showed that the increase in the use of additive types "x", foam agents and coconut fibers caused the weight of the concrete to be heavier and compressive strength. The highest weight of this lightweight concrete at the age of 28 days is not immersed in 1.867 kg / m3, while the lowest is 1.665 kg / m3. The test object for non-soaked conditions has a better compressive strength of 324 kg / cm2 than the test object with the condition soaked press test which is 293 kg / cm2.